Radiation-induced astrocyte senescence is rescued by Δ133p53. Issue 4 (4th January 2019) - Turnquist, Casmir; Beck, Jessica A; Horikawa, Izumi; Obiorah, Ifeyinwa E; Von Muhlinen, Natalia; Vojtesek, Borivoj; Lane, David P; Grunseich, Christopher; Chahine, Joeffrey J; Ames, Heather M; Smart, Dee Dee; Harris, Brent T; et al.
Abstract: Background: Cellular senescence and the senescence-associated secretory phenotype (SASP) may contribute to the development of radiation therapy–associated side effects in the lung and blood vessels by promoting chronic inflammation. In the brain, inflammation contributes to the development of neurologic disease, including Alzheimer's disease. In this study, we investigated the roles of cellular senescence and Δ133p53, an inhibitory isoform of p53, in radiation-induced brain injury. Methods: Senescent cell types in irradiated human brain were identified with immunohistochemical labeling of senescence-associated proteins p16 INK4A and heterochromatin protein Hp1γ in 13 patient cases, including 7 irradiated samples. To investigate the impact of radiation on astrocytes specifically, primary human astrocytes were irradiated and examined for expression of Δ133p53 and induction of SASP. Lentiviral expression of ∆133p53 was performed to investigate its role in regulating radiation-induced cellular senescence and astrocyte-mediated neuroinflammation. Results: Astrocytes expressing p16 INK4A and Hp1γ were identified in all irradiated tissues, were increased in number in irradiated compared with untreated cancer patient tissues, and had higher labeling intensity in irradiated tissues compared with age-matched controls. Human astrocytes irradiated in vitro also experience induction of cellular senescence, have diminished Δ133p53, and adopt a neurotoxic phenotype as demonstrated by increased senescence-associated beta-galactosidase activity, p16 INK4A, and interleukin (IL)-6. In human astrocytes, Δ133p53 inhibits radiation-induced senescence, promotes DNA double-strand break repair, and prevents astrocyte-mediated neuroinflammation and neurotoxicity. Conclusions: Restoring expression of the endogenous p53 isoform, ∆133p53, protects astrocytes from radiation-induced senescence, promotes DNA repair, and inhibits astrocyte-mediated neuroinflammation.